In the name of Osama bin Laden: global terrorism & the bin Laden brotherhood - Jacquard, Roland (Duke University Press, 2002)
A young man from a good family -- From Riyadh to Peshawar -- Banished to Sudan -- Among the Taliban -- The Islamic Legion -- The anti-American crusade -- Target: bin Laden -- Osama bin Laden confronts the Arab world -- The bin Laden brotherhood -- Asian fever -- The bin Laden network's billions -- Drugs and terrorism -- Jihad's new weapons.